A healthy settings approach to addressing painogenic environments: New perspectives from health promotion - Johnson, Mark I.; Woodall, James (Frontiers in Pain Research, 2022)
Structural approaches to promoting health focus on policies and practices affecting health at the community level and concentrate on systems and forces of society, including distribution of power, that foster disadvantage and diminish health and well-being. In this paper we advocate consideration of structural approaches to explore macro level influences on the burden of persistent pain on society. We argue that health promotion is an appropriate discipline to ameliorate painogenic environments and that a “settings approach” offers a crucial vehicle to do this. We encourage consideration of socio-ecological frameworks to explore factors affecting human development at individual, interpersonal, organizational, societal, and environmental levels because persistent pain is multifaceted and complex and unlikely to be understood from a single level of analysis. We acknowledge criticisms that the structural approach may appear unachievable due to its heavy reliance on inter-sectoral collaboration. We argue that a settings approach may offer solutions because it straddles “practical” and cross-sectorial forces impacting on the health of people. A healthy settings approach invests in social systems where health is not the primary remit and utilises synergistic action between settings to promote greater health gains. We offer the example of obesogenic environments being a useful concept to develop strategies to tackle childhood obesity in school-settings, community-settings, shops, and sports clubs; and that this settings approach has been more effective than one organisation tackling the issue in isolation. We argue that a settings approach should prove useful for understanding painogenic environments and tackling the burden of persistent pain.